Systematic review on badminton injuries: incidence, characteristics and risk factors - Stepper, B.; Hecksteden, A.; Stagge, H.; Faude, O.; Donath, L. (BMJ Open Sport & Exercise Medicine, 2025)
Objectives As a high-intensity intermittent sport with short and repeated rapid accelerations, decelerations and changes of direction, badminton involves high joint and muscle loads. This review aims to identify relevant injury risk characteristics and factors that facilitate developing and implementing badminton-specific injury prevention programmes.